Analisis Pewilayahan Komoditi Pertanian Berbasis Produksi di Kabupaten Banggai - Lige, Firga Nabila; Lihawa, Fitryane; Karim, Wahyudin Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The research objective was to know the agricultural commodity zoning by using the production approach, to know the distribution map of agricultural commodity and to know a carrying capacity agricultural land in Banggai District. The research has been conducted in Banggai District, Central Sulawesi. It applied the survey method. The data analysis used regional economic approach numely analysis of Localization, Specialization, and Basis (Location Quotient o: 1.Q) with data of agricultural commodity production total in Banggai District of Central Sulawesi. The e finding of research 3 of research showed that the agricultural commodity zoning was spread throughout regions in Banggai District while the specialization of agricultural commodity distribution in Banggai District for special food crop was corn, for horticulture was cayenne pepper, for the plantation was tall coconut, and for livestock was kampung chicken. Meanwhile, the basis of food crops in Banggai District was com as found in 15 sub-districts (65.22%). basis of horticulture was long beans as found in 13 sub-districts (56.5%). basis of plantation was tall coconut as found in 13 sub-districts (56.5%), and basis of livestock namely free range chiken in Banggai District was found in 19 sub-districts (82.61%).